Brand reputation management and brand experience towards reputation of Malaysian polytechnics / Nur Azreen Azriana Azham and Tg. Aroal Hawa Delaila Tg Ahmad - Azham, Nur Azreen Azriana; Tg Ahmad, Tg. Aroal Hawa Delaila (Universiti Teknologi MARA, Perlis, 2020)
In higher education, reputation management is essential to ensure the higher education institutions continue relevant and significant in the eye of the shareholders worldwide. There are many efforts to increase reputation by improving the ranking in the world level. Currently, the brand reputation (BR) of higher institution cannot be proud of yet as BR management is critical in growing a business or service. The research aim to identify the relationship between brand culture (BC), brand expression (BE) and brand experience (BEX) regarding polytechnic BR among polytechnic students of the northern region in Malaysia. In addition, this research also aims to identify which of the variables has the strongest relationship with BR among polytechnic students. The study employs a quantitative method. 378 questionnaires were distributed to polytechnic students of the northern region. The study resulted a significant relationship between BC, BE and BEX in the BR of polytechnic's students. Based on these results, it is found that BC has the strongest relationship with BR among polytechnic's students of the northern region in Malaysia. The findings from this research can be used by next researchers, practitioners, government, university authority as well as academician, as guidance for them to manage well their BR.